Implementation of QRIS as a Digital Payment System Based on Sharia Principles - Rukiyah; Wargo; Kuswanto (Zabags Qu Publish, 2025)
The rapid digital transformation of payment systems has accelerated the shift from cash to more efficient non-cash instruments, notably through the Quick Response Code Indonesian Standard (QRIS) initiated by Bank Indonesia. This study examines the implementation of QRIS as a digital payment system in Tanjung Jabung Timur and evaluates its alignment with Sharia principles. Employing a qualitative phenomenological approach, the research draws on in-depth interviews, direct observations, and documentation involving QRIS users, both merchants and consumers, selected via purposive sampling. Findings indicate that Muslim communities in the region perceive QRIS positively due to its convenience, transactional efficiency, and the transparency and security it provides in financial recordkeeping. Identified constraints include uneven internet infrastructure and limited digital literacy. From an Islamic jurisprudence perspective, QRIS is viewed as consistent with muamalah principles, avoiding riba, gharar, and maisir, and fitting within valid contractual frameworks of sale (bay‘) and leasing of services (ijarah). The study contributes to the literature on integrating financial technology with Sharia compliance and offers practical implications for regulators, payment service providers, and businesses to strengthen Sharia-compliant financial inclusion in Indonesia.